Analisis Putusan Hakim Nomor 54/Pid/2019/Pt. Jap. Tentang Tindak Pidana Makar Oleh Organisasi Papua Merdeka Perspektif Hukum Pidana Islam - Iskandar, Muhamad Bagas Goval; Ajazy, Yusup; Sumardi, Didi (Jurnal Impresi Indonesia, 2025)
This article discusses the criminal case of treason committed by members of the West Papua National Committee (KNPB) as decided in Case Number 54/Pid/2019/PT. JAP. The study analyzes the judge's legal considerations and assesses the criminal act from the perspective of Islamic criminal law, particularly the concept of al-baghyu. The analysis is further enhanced through the framework of maq??id al-shar?‘ah to explore how the law protects religion, life, and property. The research applies a normative juridical method with a qualitative descriptive approach. It concludes that both Indonesian positive law and Islamic law emphasize the need for firm yet fair responses to treason, including the option of reconciliation.